Relationship between Working Capital Management Efficiency and Long-Term Financial Performance - Antonio Oliveira de Carvalho; Camila Carvalho Olivera; Ivano Ribeiro (Journal of Business Management and Economics, 2019)
In corporate financial management, short-term financial performance involving collection and conversion of assets (assets and rights) into cash in order to meet short-term financial obligations, termed as liquidity, is of key importance for the balance and short-term financial health, as well as for attaining long-term financial performance (profitability and return). The purpose of this article is to analyze the existing correlation between liquidity, stemming from the Current Liquidity Ratio - CLR and Net Profit Margin – NPM (profitability) and Return on Assets - ROA (return). Indicators from seven fiscal years were analyzed during the economic crisis period (2011 to 2017) of twelve Brazilian publicly-traded companies, of three different sectors, with shares negotiated on the BM & FBovespa. Analyzes were performed in two phases, the first being a graphical analysis of the CLR, NPM and ROA indicators and the trends throughout the period under analysis. During the second phase a correlation analysis was performed – Spearman correlation coefficient – with the use of the SPSS software. The results obtained indicate a correlation between the liquidity, profitability and return indicators.